2002
DOI: 10.1002/1522-2632(200207)87:4<439::aid-iroh439>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Pico-, Nano-, Microplankton Abundance and Primary Productivity in a Eutrophic Coastal Area of the Aegean Sea, Mediterranean

Abstract: Primary productivity, pico‐, nano‐, microplankton and key environmental factors were studied in a eutrophic coastal area of the Aegean Sea during the winter – spring period. Primary productivity reached high values and showed similar trends of change to those of nanophytoplankton abundance. Nano‐ and microplankton cell densities showed high variability while picoplankton abundance was kept relatively stable. Diatoms dominated nanophytoplankton for most of the winter – spring period while a shift to dinoflagell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
2
14
0
4
Order By: Relevance
“…A modeling experiment in this part showed that under nutrient enrichment diatoms contribute %2/3 of the total phytoplankton biomass followed by picoplankton and flagellates. This is in accordance with observations in the semi-enclosed gulf of Thermaikos where diatoms formed most of the reported algal blooms (Mihalatou & Moustaka-Gouni, 2002).…”
Section: Chlorophyll-asupporting
confidence: 93%
See 2 more Smart Citations
“…A modeling experiment in this part showed that under nutrient enrichment diatoms contribute %2/3 of the total phytoplankton biomass followed by picoplankton and flagellates. This is in accordance with observations in the semi-enclosed gulf of Thermaikos where diatoms formed most of the reported algal blooms (Mihalatou & Moustaka-Gouni, 2002).…”
Section: Chlorophyll-asupporting
confidence: 93%
“…14) are very close to the field measured range of 5-23 and 0.2-4.5 lg/l/d, respectively (Pancucci-Papadopoulou & Christaki, 2000) with higher rates during winter to spring for phytoplankton and middle of spring for bacteria at both areas. Highest primary production rates in January were also recorded in Thermaikos (Mihalatou & Moustaka-Gouni, 2002). At the more eutrophic internal station throughout the year the primary producers exhibit much higher rates compared to bacteria without any significant variability with depth.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Field and experimental procedures. Marine and freshwater plankton samples from Thermaikos Bay and from the university pool, respectively, were collected weekly from surface water in accordance with Mihalatou & Moustaka-Gouni (2002) Airborne particles were recovered during the same period using an air sampler which collected air at a rate of 16 l min -1 . The air was drawn into a conical flask containing 300 ml of sterile distilled water, and airborne particles were trapped and collected in the water.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, relatively few studies on primary productivity and pico-, nano-, and microplankton abundance have been published (Kormas et al 1998;Robinson 2000;Mihalatou and Moustaka-Gouni 2002). The population structure and dynamics are greatly influenced by the different hydrographic conditions prevailing in the northern and southern Aegean Sea due to the influence of Black Sea and Levantine Sea waters, respectively.…”
Section: Introductionmentioning
confidence: 99%